Modulation of stress-, pain-, and alcohol-related behaviors by perineuronal nets - Jhoan S. Aguilar; Amy W. Lasek (Neurobiology of Stress)
Perineuronal nets (PNNs) are a special form of central nervous system extracellular matrix enriched in hyaluronan, chondroitin sulfate proteoglycans, tenascins, and link proteins that regulate synaptic plasticity. Most PNNs in the brain surround parvalbumin-expressing inhibitory interneurons, which tightly regulate excitatory/inhibitory balance and brain activity associated with optimal cognitive functioning. Alterations in PNNs have been observed in neurological diseases and psychiatric disorders, suggesting that they may be key contributors to the neuropathological progression and behavioral changes in these diseases. Alcohol use disorder (AUD), major depressive disorder (MDD), and chronic pain are highly comorbid conditions, and changes in PNNs have been observed in animal models of these disorders, as well as postmortem tissue from individuals diagnosed with AUD and MDD. This review focuses on the literature describing stress-, alcohol-, and pain-induced adaptations in PNNs, potential cellular contributors to altered PNNs, and the role of PNNs in behaviors related to these disorders. Medicines that can restore PNNs to a non-pathological state may be a novel therapeutic approach to treating chronic pain, AUD, and MDD.